👤

va rog ajutați-ma repede urgent ! ! ! ! !! ! ! ! !! ! ! ! !!! !​

Va Rog Ajutațima Repede Urgent class=

Răspuns :

[tex](26 + (x - 7) \times 12) \div 2 = 49[/tex]

[tex](26 + 12x - 84) \div 2 = 49[/tex]

[tex]( - 58 + 12x) \div 2 = 49[/tex]

[tex] \frac{ - 58 + 12x}{2} = 49 [/tex]

[tex] \frac{2( - 29 + 6x)}{2} = 49 [/tex]

[tex] - 29 + 6x = 49[/tex]

[tex]6x = 49 + 29[/tex]

[tex]6x = 78[/tex]

[tex]x = 13[/tex]

Explicație pas cu pas:

[26+(×-7)*12]:2=49

(26+12×-84):2=49

(-58+12×):2=49

[tex] \frac{ - 58 + 12x}{2} = 49[/tex]

[tex] \frac{2( - 29 + 6x)}{2} = 49[/tex]

simplificam 2 cu 2

-29+6×=49

6×=49+29

6×=78

×=78:6

×=13